THE EFFECT OF CAREER DEVELOPMENT, MOTIVATION AND ORGANIZATION’S COMMITMENT OH WORK SATISFACTION - Efendi; Fitri Maysaroh (Human Capital Development, 2018)
Purpose- The purpose of this study was to analyze the influence of career development, motivation, and organizational commitment jointly or partially on employee job satisfaction, and to find out which variables most influence employee job satisfaction. The data used is primary data using a questionnaire. Design/methology/approach- The population of this study were all employees at the Sheraton Grand Hotel Jakarta Gandaria City. The sample was taken by accidental sampling as many as 100 respondents. The analytical tool used in this study is the test of validity, reliability and multiple linear regression. Findings- The results of this analysis mention that career development, motivation, organizational commitment simultaneously have a significant influence on employee job satisfaction at the Sheraton Grand Jakarta Gandaria City Hotel. And partially career development, motivation, organizational commitment have a significant influence on employee job satisfaction decisions at the Grand Jakarta Gandaria City Hotel.